Feuerbach, religion and post-theism - Beyers, Jaco (HTS teologiese studies, 2022)
How subject and object relate is perceived differently. This has been identified and discussed by philosophers. Hegel built on Plato’s notion that true reality only exists in ideas and is, therefore, objectively true. Hegel argued that the world we encounter is the objectification of the divine mind. Empiricists argue that material things can be engaged through the senses and are, therefore, real. But how do we know that spiritual things are real since they cannot be engaged through the senses? Feuerbach reacted against the Enlightenment thoughts of his time by postulating that god is not real since it is a projection of human qualities. Feuerbach inverted Hegel’s theory by stating that the divine is an abstraction and reification of human thought. With this theory, Feuerbach stated that religion is human-made and redundant. Feuerbach’s theory of the non-existence of god was created during the 19th century and corresponds with post-theism. De Botton also denies the existence of god, but declared that religion has many valuable functions for society. Feuerbach, from a philosophical and De Botton, from a sociological perspective, both deny the existence of god, but differ on the role religion play in society. Feuerbach’s theories proves to have relevance to current studies of religion.Contribution: This contribution investigates the position of Ludwig Feuerbach and tries to indicate the influence his ideas had on current post-theistic theories, such as that by Allan de Botton.